Adventure tourism: opportunities and management challenges for SADC destinations - Tracey McKay (Acta Academica, 2013)
The international tourism industry is becoming increasingly segmented with the growth of different ‘niches’ or ‘segments’ of tourism. One notable and rapidly expanding niche segment in the international tourism economy is that of adventure tourism. Although adventure tourism has attracted a growing international scholarship, research on adventure tourism in Africa is currently undeveloped. Despite this, all Southern African Development Community (SADC) states are promoting themselves as adventure tourism destinations. This article identifies seven key management and policy issues relating to the development of the adventure tourism business in the SADC region.